making public distribution system more effective - Sud, Surinder
The study makes a case against a uniform system of public distribution system because of its magnitude and operational complications. It draws attention to short term entitlement slips for the vulnerable sections of the population as against the system of permanent ration cards. Therefore, it is suggested that the inclusion of clothes and medicines along with essential items in rural areas
Keywords: PDS; Rationing; Public Distribution System